Role Of Pratimarsha Nasya Inmukhdushika Management: A Case Study - Tetarwal, Poonam; Samagandi, Kashinath; Sharma, Kamalesh Kumar (International Research Journal of Ayurveda & Yoga, 2024)
CASE SUMMARY- Mukhdushika is a disease which devastate beauty(excellence) of face which, in the end diminishes confidence of an individual. In texts of Ayurveda it is described as “shalmalikantak”, where shalmalikantak means small thorns seen on the bark of shalmali tree (salmaliaindica). Most resembling condition with Mukhdushika is acne (acne vulgaris). A 25-year-old girl presented on 21-12-18 in Swasthavrittaopd of NIA (National Institute of Ayurveda) with severe acne and scars on her face. Anutaila is used in all Urdhvajatrugatarogas. As Mukhdushika is a urdhvajatrugata disease therefore, Anu Taila is selected for pratimarshnasya in this case. Anu tailapratimarshanasya was advised to the patient 2 drops in each nostril by the help of a dropper, twice a day morning and evening for 21 days. No other medication or pathyaapathya advice was given to patient. After trial it shown that pratimarshanasya causes decrease in acne number, size and grade. Hence, PratimarshaNasya of anutaila is highly effective treatment due to subsiding symptoms of Mukhdushika (acne vulgaris).